225k views
0 votes
-3(x+0.6)=6(x+2.4)
Could you possibly show the work also?

User Rohan Bari
by
5.5k points

1 Answer

6 votes
Multiple-3(x+0.6) and 6(x+2.4) you will get -3x-1.8=6x+14.4 then you add -3x + 6x you will get -9x=14.4+1.8 you add 14.4+1.8 that will give you 16.2 then divide that by -9
-3(x+0.6)=6(x+2.4) Could you possibly show the work also?-example-1
User Marques
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.